PENERAPAN HYGIENE DAN SANITASI PASTRY DI HOTEL KOTA TASIKMALAYA - Indah Sugiarti (Bajang Institute, 2024)
Implementing hygiene and sanitation at hotels in Tasikmalaya is an important effort that must be considered in theimplementation process. This research focuses on the implementation of Hygiene and Sanitation in Hotels in Tasikmalaya. This research uses qualitative descriptive methods, interview methods, observation and document study. The conclusion of this research is that hygiene and sanitation standards have been implemented in hotels in Tasikmalaya